Programa bolsa família: uma análise dos motivos que levaram ao desligamento de um grupo de beneficiários no município de Santo Ângelo/RS - Pretto, Diego (2015)
The study sought to evaluate the efectiveness of Bolsa Família Program through the analysis of the reasons that are responsible for the termination of former beneficiary families in the city of Santo Ângelo (RS), among the years from 2009 to 2013, as well as correlate them with complementary programs, in order to identify whether the program has criated emancipation conditions, or whether the situation is linked to external order factors. For this, an exploratory research of cross-sectional cut has been realized with 237 former beneficiary families. The results revealed that the predominant reason for the termination from the program was the increasing in the household incomes per capita, and this result has been originated by the granting pensions, folloew by the insertion in the labor market, while the complementary programs have been shown pratically without effect for the former beneficiaries inclusion in the labor market, whereas the productivity inclusion has been linked in large part to the commitment of the families in the search for better life conditions. Moreover, the period of benefic reception, the reasons for the exclusion from the program and the perception of the interviewees confirm the idea of continuous dependence into the benefit. However, in the benefit receiving time, positive repercursions have shown up, mainly, related to the improvement in the food condition, the school attendance has increased and the household budget has reinforced. In this way, it is concluded that, the program is, nowadays, in compensatory and distribuction policy to the detriment of its developmental aspects, being subject to adjustment in the instituction design.